2009
DOI: 10.3945/ajcn.2008.26598
|View full text |Cite
|
Sign up to set email alerts
|

Dietary sources of vitamin B-12 and their association with plasma vitamin B-12 concentrations in the general population: the Hordaland Homocysteine Study

Abstract: Dietary intake of dairy products and fish are significant contributors to plasma vitamin B-12 and may improve plasma vitamin B-12 status. Vitamin B-12 appears to be more bioavailable from dairy products; guidelines for improving vitamin B-12 status should take this into consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
116
5
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(134 citation statements)
references
References 45 publications
11
116
5
2
Order By: Relevance
“…In the Czech Republic reported mean levels of serum vitamin B 12 were comparable to those in other European countries, such as Norway (40) , and above the reference value (150 pmol/l). These findings are consistent with the vitamin B 12 intake results from the present study (Fig.…”
Section: Comparison Of Micronutrient Statusmentioning
confidence: 63%
“…In the Czech Republic reported mean levels of serum vitamin B 12 were comparable to those in other European countries, such as Norway (40) , and above the reference value (150 pmol/l). These findings are consistent with the vitamin B 12 intake results from the present study (Fig.…”
Section: Comparison Of Micronutrient Statusmentioning
confidence: 63%
“…Thus, HO-B12 is a ubiquitous and sometimes predominant form of B12 in food [1]. The daily supply of B12 in a Western omnivorous diet is around 6 µg [3,4], well above the recommended daily allowance (RDA) of 2.4 µg [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, the relationship with intake from meat, poultry or fish is weaker (5) . A Norwegian study showed that plasma vitamin B 12 increases with the amounts of vitamin B 12 provided by dairy products or fish but not with those provided by eggs or meat (6) . Moreover, for a similar intake, plasma concentrations of vitamin B 12 were higher when the vitamin was supplied by dairy products than by fish, suggesting that the bioavailability of the vitamin from dairy products is higher than from the other sources (6) .…”
mentioning
confidence: 99%
“…A Norwegian study showed that plasma vitamin B 12 increases with the amounts of vitamin B 12 provided by dairy products or fish but not with those provided by eggs or meat (6) . Moreover, for a similar intake, plasma concentrations of vitamin B 12 were higher when the vitamin was supplied by dairy products than by fish, suggesting that the bioavailability of the vitamin from dairy products is higher than from the other sources (6) . Indeed, these retrospective studies seem to indicate that vitamin B 12 supplied by dairy products is more available than from other natural sources, although in these studies, intake data were obtained by a FFQ.…”
mentioning
confidence: 99%